A Model of Eco-Efficiency and Recycling - Mario Cogoy (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
This paper presents the model of an economy subject to the mass conservation principle. The economic system is related to the environment by a flow of virgin materials into the economy, and by the diffusion of waste into the environment. Ecoefficiency contributes to reducing material waste in all processes. Recycling can reduce the diffusion of waste by feeding it back into the economy. Human capital enhances productivity, eco-efficiency and the quality of all kinds of outputs. Recycling and human capital formation use productive factors and are rooted therefore, as all other activities, in the material basis of the economy. The paper studies an optimal material state of society.
Keywords: D90; O30; O41; Q00; 330; Eco-efficiency; recycling; materials balances; material flows; knowledge; Öko-Effizienz; Stoffstrom-Management; Recycling; Bildungsinvestition; Umweltökonomik; Theorie